Influência do uso do sistema de mensuração de desempenho na ambidestria organizacional e no desempenho no setor de software - Severgnini, Elizandra (2016)
The performance measurement system (SMD) can perform different functions within an organization, including paradoxical functions. On the one hand, some functions are focused on the control and monitoring of activities performed in companies. On the other hand, some functions may be aimed at the pursuit of innovation, experimentation and the development of creativity. When the union of these different forms of use of PMS is found in companies, there is evidence of an ambidextrous organization capable of improving their products or services, while at the same time developing innovation. Although it is a recent theme in management literature, organizational ambidexterity has gained significant emphasis in recent years. Recent studies have shown that managerial control systems may be able to promote organizational ambidexterity. This work seeks to examine the relationship between different types of PMS use, organizational ambidexterity and performance. The research is quantitative and employs descriptive statistical techniques and structural equation modeling to analyze the data obtained from the 227 Brazilian software companies, using a survey to collect data. The results show that this study amplifies previous researches of managerial accounting using the contingency approach to examine the mediation of the organizational ambidexterity between the use of PMS and the organizational performance. One of the evidences suggested in this study is that the use of PMS in order to focus attention, make decisions and legitimize tends to influence the organizational ambidexterity, which, in turn, influences performance. However, a surprise in the results was evidenced: when performance information is used for monitoring purposes, the effects on both organizational performance and organizational ambidexterity are not significant. Finally, this study contributes to the emerging line of research that provides empirical tests examining the tension dynamics generated by the interaction of different types of PMS use.